Effect of curing Helicobacter pylori infection on intragastric pH during treatment with omeprazole. Issue 6 (December 1995) - Verdú, E F; Armstrong, D; Idström, J P; Labenz, J; Stolte, M; Dorta, G; Börsch, G; Blum, A L
Abstract : It has been shown that omeprazole treatment produces higher intragastric pH values in Helicobacter pylori positive subjects than in H pylori negative subjects. This study aimed to investigate the effect of curing H pylori on the intragastric pH in both the presence and absence of omeprazole therapy. Twenty four hour intragastric pH recordings were performed before and after a one week course of omeprazole (20 mg once daily) in 18 H pylori positive subjects and were repeated after the infection had been cured. In the absence of omeprazole, the total 24 hour pH values before cure did not differ from those afterwards. During omeprazole treatment the 24 hour pH values were much higher before (median (95% CI) 5.4: 4.3, 6.0), than after cure of infection (3.6: 2.1, 4.4; p < 0.001). The omeprazole induced fall in H+ activity before cure of H pylori did not, however, differ from that afterwards. It is concluded that the apparently greater antisecretory effect of omeprazole during H pylori infection may be a result of the production of acid neutralising compounds by the H pylori. Although a direct interaction between H pylori and omeprazole cannot be excluded, it seems unlikely.